Entrepreneurship Education and Other Exogenous Variables in the Theory of Planned Behavior Model: A Systematic Literature Review - Rustiana (Faculty of Economics and Business, Universitas Gadjah Mada, 2025)
Introduction/Main Objectives: The aim of the study is to: 1) identify the role entrepreneurship education (EE) in the theory of planned behavior (TPB) model, and how it enhances students’ entrepreneurship intention (EI), 2) identify various other exogenous variables commonly paired with EE that increase EI, 3) map the various roles of EE and the exogenous variables in improving students’ EI into a single model. Background Problems: What is the role of entrepreneurship education and the exogenous variables in the TPB model, and how do they increase students’ entrepreneurship intention? Novelty: This paper’s novel contributions include 1) filling the knowledge gap in the field of entrepreneurship related to the TPB model, 2) proposing a map to depict the integration of EE and other exogenous variables into the TPB model, to make one comprehensive model. Research Methods: The data sets were drawn from the Scopus database with a systematic literature review approach, with a protocol that used the keywords